The role of attitudes in the development of Russian as a foreign language: A retrospective study - Bátyi, Szilvia (Studies in Second Language Learning and Teaching, 2017)
The article reports the findings of a retrospective study which looked at Hungarian learners’ attitudes towards Russian people, the Russian language and teachers of Russian. Mixed-methods sequential explanatory design (Ivankova, Creswell, & Stick, 2006) was applied which combines the collection and analysis of quantitative and qualitative data in two consecutive phases. First person accounts turned out to be a useful and relevant resource for exploring individual differences in proficiency in Russian. Differences in attitudes appear to play a role in the developmental process, but to what extent this refers to attrition or non-acquisition is unclear.